Insights Beyond the Revolution of Iran: A Review of Moral and Philosophical Values in the Political Realm of Imam Ayatollah Khomeini - Ahmad Kholil; Moh. Zawawi; Indah Rarasati; Djody Firmansyah (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2024)
The Islamic Revolution in Iran serves as a notable example of the erosion of moral values and political ethics. This study aims to assess the effectiveness of Imam Khomeini's concept of Wilāyah al-Faqīh in relation to the moral philosophy that underpins a nation. The research primarily employs library sources and utilizes a descriptive analysis method. The primary data consists of Imam Khomeini's thoughts on Wilāyah al-Faqīh, as articulated in his work Hukumat-e Islami: Velayat-e Faqih. Secondary data is drawn from his other writings, such as Islam and Revolution: Islamic Government along with additional relevant literature. The data collection process involves several steps: identifying literature that discusses Imam Khomeini's thought, reading and concentrating on his ideas, noting key points, and seeking other pertinent references. The data analysis employs content analysis and hermeneutic models, which are conducted in three main stages: data reduction, presentation, and conclusion drawing. The findings of this research uncover a profound relationship between Islamic political ethics and Imam Khomeini's concept of Wilāyah al-Faqīh. In a government based on Wilāyah al-Faqīh, there is no separation between religion and politics, as both realms share the common objective of establishing a just society rooted in God's law. For Imam Khomeini, politics is an extension of ethics, whereby ethics encompasses both individual conduct and social responsibilities.